Fast-Evolving Mitochondrial DNA in Ceriantharia: A Reflection of Hexacorallia Paraphyly? - Stampar, Sérgio Nascimento [UNESP]; Maronna, Maximiliano M.; Kitahara, Marcelo V.; Reimer, James D.; Morandini, Andre C. (Public Library Science, 2014)
The low evolutionary rate of mitochondrial genes in Anthozoa has challenged their utility for phylogenetic and systematic purposes, especially for DNA barcoding. However, the evolutionary rate of Ceriantharia, one of the most enigmatic orders'' within Anthozoa, has never been specifically examined. In this study, the divergence of mitochondrial DNA of Ceriantharia was compared to members of other Anthozoa and Medusozoa groups. In addition, nuclear markers were used to check the relative phylogenetic position of Ceriantharia in relation to other Cnidaria members. The results demonstrated a pattern of divergence of mitochondrial DNA completely different from those estimated for other anthozoans, and phylogenetic analyses indicate that Ceriantharia is not included within hexacorallians in most performed analyses. Thus, we propose that the Ceriantharia should be addressed as a separate clade.